International, transdisciplinary and intercultural cooperation in bioindication and biomonitoring studies (B&B Technologies). With specific consideration of plant organisms and chemical elements - Markert, Bernd (2014)
Bioindication and biomonitoring methods (B & B technologies) have been used in environmental quality assessments for many decades. The international cooperation in between various scientific teams throughout the world has produced common ideas, highly innovative results and common scientific definitions. Bioindicators (biomonitors) are organisms or communities of organisms whose content of certain chemical elements or compounds and/or whose morphological, histological or cellular structure, metabolic-biochemical processes, behaviour or population structure(s), including changes in these parameters, supply (quantitative) information on the quality of the environment or the nature of environmental changes. Bioindication compares relative (absolute) data of information (e.g. contamination) to each other. In this article, clear cut definitions of terms relevant for the practical use of B & B technologies are presented. Additionally, different uptake activities in living organisms as a function of substrate concentration are given. Physiological functions are compared by effects of acute and chronic doses of toxic substances on living systems. Future work should and must be focused on integrative B & B technologies because a) contamination can entail a large number of inorganic and organic chemicals, b) a large number of environmental monitoring problems, and c) a single bioindicator / biomonitor will not provide any meaningful information. Integrative and transdisciplinary concepts such as the Multi-Markered-Bioindication-Concept (MMBC) provide basic means to get into precautionary environmental protection effects. For further development of B & B methods, highest personal energy has to be given by teachers of universities and other institutions to students and to convince (strategically) decision makers as politicians to invest (financially) in the development of education and research of this innovative technique. Young people have to be intensively convinced on the meaning of our scientific doing, e.g. by extended forms of education. One example of multilingual education of students on a global scale and perspective is given here, meeting their emotional and rational intelligence. So, young people can find innovative scientific ideas by a strong international relevance to get mentally convinced by a profitable biological green technique. Students will be motivated to move scientifically and professionally into our international working field. In addition to this form of international scientific exchange we find an excellent side-effect pertinent to intercultural exchange.